Dose-risk relationships between cigarette smoking and cervical cancer: a systematic review and meta-analysis. Issue 2 (10th November 2022) - Malevolti, Maria Chiara; Lugo, Alessandra; Scala, Marco; Gallus, Silvano; Gorini, Giuseppe; Lachi, Alessio; Carreras, Giulia
Abstract : Objective: Cervical cancer (CC) is the fourth most frequent cancer worldwide. Cigarette smoking has been shown to influence CC risk in conjunction with human papillomavirus (HPV) infection. The aim of this study is to provide the most accurate and updated estimate of this association and its dose-response relationship. Methods: Using an innovative approach for the identification of original publications, we conducted a systematic review and meta-analysis of studies published up to January 2021. Random effects models were used to provide pooled relative risks (RRs) of CC for smoking status. Dose-response relationships were evaluated using one-stage random effects models with linear or restricted cubic splines models. Results: We included 109 studies providing a pooled RR of invasive CC and preinvasive lesions, respectively, of 1.70 [95% confidence interval (CI), 1.53–1.88] and 2.11 (95% CI, 1.85–2.39) for current versus never smokers, and, respectively, 1.13 (95% CI, 1.02–1.24) and 1.29 (95% CI, 1.15–1.46) for former versus never smokers. Considering HPV does not alter the positive association or its magnitude. Risks of CC sharply increased with few cigarettes (for 10 cigarettes/day, RR = 1.72; 95% CI, 1.34–2.20 for invasive CC and RR = 2.13; 95% CI, 1.86–2.44 for precancerous lesions). The risk of CC increased with pack-years and smoking duration and decreased linearly with time since quitting, reaching that of never smokers about 15 years after quitting. Conclusion: This comprehensive review and meta-analysis confirmed the association of smoking with CC, independently from HPV infection. Such association rose sharply with smoking intensity and decreased after smoking cessation.